2004
DOI: 10.1002/jsfa.2026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various processing techniques and different levels of antioxidant on stability of rice bran during storage

Abstract: Rice bran is a major cereal by-product available for animal feeding in many parts of the world. It has a good balance of protein, fat, carbohydrates, fiber, vitamins and minerals. The greatest restriction to the use of rice bran is its instability during storage, leading to rancidity and the presence of heat-labile antinutritional factors. Rice bran was treated to stabilize it by extrusion cooking, roasting, pelleting and adding antioxidant (125, 250 and 375 ppm). The rice bran so treated was stored for 345 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
3
10
0
1
Order By: Relevance
“…This is in agreement with other studies (Mujahid et al, 2005). The processing of RB by autoclaving resulted in some improvement in digestibility parameters.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with other studies (Mujahid et al, 2005). The processing of RB by autoclaving resulted in some improvement in digestibility parameters.…”
Section: Discussionsupporting
confidence: 93%
“…The results for the performance in the present study were in agreement with the findings of Mujahid et al (2005), who reported that increasing the levels of RB in broiler chicken diets caused significant decreases in BWG and FI. There is a relationship between the rate of feed passage through the intestine and FI in young chickens (Almirall & Garcia, 1994).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Malekian et al reported that the FFA content of raw bran stored in zip‐loc bags for 8 weeks increased from 3.7 to 22.2%. Mujahid et al found an initial FFA content of 9.5% in raw rice bran, which increased to 96.8% at the end of 345 days of storage. These different results may be due to differences in rice cultivar, FFA determination method and/or milling and storage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Whole grain foods contain high quality fatty acids like mono-unsaturated fatty acids, but their susceptibility to, and products of, rancidity are poorly understood. The majority of research relating grain composition and enzyme activity to rancidity, and decreasing rancidity via different treatments, has focused on common grains like rice (Amarasinghe, 2009;da Silva, 2006;Goffman & Bergman, 2003a;Gopinger, 2015;Malekian et al, 2000;Mujahid A, 2005;Nordin, 2014;Prabhakar, 1986;Sharma, 2004) and wheat (A. Doblado-Maldonado, Arndt, & Rose, 2012;Posner & Hibbs, 2005;Srivastava, 2007;B. Xu et al, 2013).…”
Section: Markers Of Ranciditymentioning
confidence: 99%